Europeanising the governance of religious diversity: an institutionalist account of Muslim struggles for public recognition - Koenig, Matthias (Journal of ethnic and migration studies, 2007)
Recent comparative social science research has emphasised that different patterns of incorporating Muslim migrant minorities are related to institutional varieties of religious governance in Western European countries. This article focuses on the emergence of institutional elements of religious governance at the European level and their impact on the organisational and symbolic incorporation of Muslims. Drawing on conceptual tools from institutional theories in sociology, it is argued that the emergence of highly differentiated institutional domains of law, politics and identity at the European level has resulted in the convergence of basic legal principles of religious governance as well as in the persistence of divergent national patterns of incorporating religious minorities. These contradictory trends explain specific features of contemporary Muslim migrants’ struggles for public recognition.